DOT-IMMUNOASSAY USING GOLD NANOPARTICLE MARKED COLLOID GOLD FOR THE DETECTION OF BOTULINIC TOXIN IN CLINICAL MATERIAL AND FOOD PRODUCTS - T. Yu. Zagoskina; E. L. Chaporgina; E. Yu. Markov; Yu. O. Popova; T. M. Dolgova; O. V. Gavrilova; T. S. Taikova; S. V. Balakhonov (Журнал микробиологии, эпидемиологии и иммунобиологии, 2017)
Aim. Construction of test-systems for dot-immunoassay using colloid gold nanoparticles as a marker of specific antibodies for the detection of botulinic toxin in clinical material and food products. Materials and methods. 20 nm gold nanoparticles were used as a marker of specific antibodies. IgGs were isolated from polyvalent diagnostic sera against type А, В, С, E, F botulin toxins produced by SPC Allergen (Stavropol) with 5000 - 10 000 ME activity. Botulin toxin in clinical material (blood sera) from 3 patients with established botulism clinical diagnosis as well as food product (home-made mushroom soup solyanka) was determined by dot immunoassay on nitrocellulose membrane. Results. Botulin toxin was detected in all the studied samples (blood sera from 3 patients and the soup) that was registered in the patient No. 1 at the 1:2112 dilution of fhe studied sample, in patient No. 2 - 1:32, in patients No. 3 - 1:1056, in the food product - 1:8. Botulin toxin was not detected in the negative control (pure cultures of the dysentery cauzative agents and intestine yersinosis, blood sera of the patient with All and a healthy individual as well as canned beans in tomato sauce and canned green peas). Conclusion. A highly sensitive specific test-system was developed for dot-immunoassay based on the commercial anti-botulin antibodies labelled with colloid gold particles that allows to detect botulin toxins within 2 hours in the sample volume of 1 - 2 microlites .